FMRI activation to cannabis odor cues is altered in individuals at risk for a cannabis use disorder. Issue 10 (30th August 2020) - Kleinhans, Natalia M.; Sweigert, Julia; Blake, Matthew; Douglass, Bradley; Doane, Braden; Reitz, Fredrick; Larimer, Mary
Abstract: Introduction: The smell of cannabis is a cue with universal relevance to cannabis users. However, most cue reactivity imaging studies have solely utilized visual images, auditory imagery scripts, or tactile cues in their experiments. This study introduces a multimodal cue reactivity paradigm that includes picture, odor, and bimodal picture + odor cues. Methods: Twenty‐eight adults at risk for cannabis use disorder (CUD; defined as at least weekly use and Substance Involvement Score of ≥4 on the Cannabis sub‐test of the Alcohol, Smoking and Substance Involvement Screening Test) and 26 cannabis‐naive controls were exposed to cannabis and floral cues during event‐related fMRI. Between‐group differences in fMRI activation and correlations were tested using FMRIB's Local Analyses of Mixed Effects and corrected for multiple comparisons using a voxelwise threshold of z  > 2.3 and a corrected cluster threshold of p  < .05. Results: Both visual and olfactory modalities resulted in significant activation of craving and reward systems, with cannabis odor cues eliciting a significantly greater response in regions mediating anticipation and reward (nucleus accumbens, pallidum, putamen, and anterior insular cortex, supplementary motor area, angular gyrus and superior frontal gyrus) and cannabis picture cues eliciting a significantly greater response in the occipital cortex and amygdala. Furthermore, the CUD group showed significantly increased activation in the ventral tegmental area (VTA), the insula, and the pallidum compared to controls. Within the CUD group, activation in the insula, anterior cingulate, and occipital cortex to bimodal cannabis cues was significantly correlated with self‐reported craving. Conclusion: Our multimodal cue reactivity paradigm is sensitive to neural adaptations associated with problematic cannabis use. Abstract : The smell of cannabis is a cue with universal relevance to cannabis users, but this modality is under‐utilized in cue reactivity research. Our fMRI study demonstrated that cannabis odor cues elicit greater activation in reward circuitry than cannabis visual cues.